2011
DOI: 10.1128/aac.01247-10
|View full text |Cite
|
Sign up to set email alerts
|

Detection of NDM-1-Producing Klebsiella pneumoniae in Kenya

Abstract: Seven carbapenem-resistant NDM-1-positive Klebsiella pneumoniae isolates were recovered from patients hospitalized between 2007 and 2009 in different wards at a referral and tertiary care center in Nairobi. Most of the isolates were obtained from urine. All isolates carried the bla NDM-1 carbapenemase gene previously reported from India, Pakistan, and the United Kingdom. These isolates were clonally related and expressed many other resistance determinants, including ␤-lactamases CTX-M-15, OXA-1, OXA-9, CMY-6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(84 citation statements)
references
References 17 publications
3
80
1
Order By: Relevance
“…Here, the RmtC enzyme was involved and was encoded by a gene located on the same plasmid carrying the bla NDM-1 gene. Such an association between those two genes was previously reported in a single K. pneumoniae isolate from India (19) and in a series of K. pneumoniae isolates from Kenya (26). A 150-kb and untypeable plasmid coharboring the two genes was similarly identified here and in the Indian isolate.…”
supporting
confidence: 54%
“…Here, the RmtC enzyme was involved and was encoded by a gene located on the same plasmid carrying the bla NDM-1 gene. Such an association between those two genes was previously reported in a single K. pneumoniae isolate from India (19) and in a series of K. pneumoniae isolates from Kenya (26). A 150-kb and untypeable plasmid coharboring the two genes was similarly identified here and in the Indian isolate.…”
supporting
confidence: 54%
“…[18] The emergence and possible spread of carbapenem-resistant Enterobacteriaceae isolates in the province would represent an additional step in the wrong direction that might be enhanced by misuse of carpabenems, as observed a few years ago in some Asian countries. [32] …”
Section: Discussionmentioning
confidence: 99%
“…The differences observed between both studies (we observed that several class A enzymes, including KPCs and MBLs, were the most undetected carbapenemases by the AES) could be due to the different carbapenems used in the cards. The discrepancy in detection of OXA-163 and OXA-48 could also be due to differences in the hydrolytic profiles of these enzymes (24).…”
Section: Vol 49 2011mentioning
confidence: 99%